A STUDY ON COMPARING BORROWER EASE WITH STATE BANK OF INDIA (SBI) AND LIFE INSURANCE CORPORATION (LIC) HOUSING FINANCE IN KRISHNAGIRI DISTRICT - D. Pazhaniammal; R. Venkatesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Everyone needs his own servant. The latter is an effective and valuable incentive for the financial turnaround of residency activities. But, buying a home in the current situation is a difficult task, as it has a significant use. A running Elegance family cannot afford the cost of this use. To take a decision on this movement, the government offers to extend housing finance to every individual at a low loan rate. The housing finance sector allows deduction in bonds. Home financing mode of housing on a credit basis in which we pay fixed payments often with high loan charges. A credit position was granted primarily based on the qualifications of the individuals and the standards of the bank. Many banks and financial institutions have entered the housing finance venues that offer modest advances at low borrowing costs. The cost of financing is an essential element of advances. Banks and economic institutions provide types of financial prices for credit ratings, for example, fixed and drifting. Banks provide housing finance as well as loans for development, growth, transformation, development etc. The main reason for this study is to think and dissect between housing finance technology and customer pleasure of SBI the largest public sector bank in India and LIC being the largest personal convenience financial institution in India.